2004
DOI: 10.1136/adc.2003.036863
|View full text |Cite
|
Sign up to set email alerts
|

Can methadone concentrations predict the severity of withdrawal in infants at risk of neonatal abstinence syndrome?

Abstract: Aim: To assess the usefulness of cord and serum methadone concentrations at 2 days of age in predicting the severity of neonatal abstinence syndrome (NAS) in infants whose mothers received methadone during pregnancy. Methods: After informed consent, infants were enrolled if they were delivered at 35 weeks gestation or greater. Relevant information was collected from maternal notes. A sample of cord blood was taken at delivery, with a follow up sample at 48 hours of age. The samples were analysed in batches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 19 publications
4
48
2
2
Order By: Relevance
“…Methadone concentrations in cord blood and at 48 hours of age, 72 as well as the rate of decline in neonatal serum concentration, 65 appear to correlate with NAS signs. Kuschel et al 72 found that infants who required rescue treatment had lower cord blood methadone concentrations and that, in all but 1 infant, methadone concentrations were undetectable in the serum at 48 hours.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Methadone concentrations in cord blood and at 48 hours of age, 72 as well as the rate of decline in neonatal serum concentration, 65 appear to correlate with NAS signs. Kuschel et al 72 found that infants who required rescue treatment had lower cord blood methadone concentrations and that, in all but 1 infant, methadone concentrations were undetectable in the serum at 48 hours.…”
mentioning
confidence: 94%
“…Some studies demonstrated that larger maternal methadone dosages in late pregnancy were associated with greater neonatal concentrations and increased risk of withdrawal, 8,9,[62][63][64][65][66][67][68] but others refuted a correlation. [69][70][71][72][73][74] This lack of consensus is explained in part by different approaches to the management of antenatal methadone maintenance therapy. There were substantial variations in the mean and range of daily methadone dose in the populations studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Among infants exposed to chronic opiates in utero, the incidence of neonatal abstinence syndrome (NAS) ranges from 21 to 94%. [4][5][6] The onset, duration and severity of NAS may be impacted by the types and degree of fetal drug exposure and by neonatal treatment strategies, [7][8][9][10][11][12][13] use of tobacco during pregnancy, 14 gestational age 15,16 and use of maternal breast milk (MBM) as the primary source of nutrition. [17][18][19][20] The interactions of these factors and the composite impact on response to pharmacologic therapy for NAS have not been adequately elucidated in a large cohort of infants.…”
Section: Introductionmentioning
confidence: 99%
“…21 While pregnant and postpartum women should be counseled in ways to reduce or quit smoking due to the association of tobacco with decreased breast milk volume and adverse fetal and neonatal outcomes (e.g., sudden infant death syndrome), they should also understand that the potential health benefits of breastfeeding likely outweigh the risks of tobacco products passing into breast milk. 9,22 Clinicians should also seek to dispel women's fears that infants can "OD" on methadone-emphasizing the proportionately small transfer of methadone through milk, 10 the poor correlation between maternal methadone dose and severity of NAS symptoms, 5,[11][12][13][23][24][25] and the mechanisms through which breastfeeding can potentially protect against NAS development (e.g., skin-to-skin contact; small transfer of methadone through breast milk). [26][27][28] It is equally imperative that clinicians communicate to women the infant health risks of unprotected sex (and HIV contraction), alcohol use, and illicit drugs while breastfeeding, as these substances pass readily into breast milk.…”
Section: Discussionmentioning
confidence: 99%